Volatile places : a sociology of communities and environmental controversies - Gunter, Valerie J. (Valerie Jan), 1961- (Pine Forge Press, 2007)
A guide to spirited public controversies that inevitably occur when environments and human communities collide. It talks about the movie "An Inconvenient Truth" based on the environmental activism of Al Gore, and the devastation of Hurricane Katrina. It offers a case study approach to the investigation of community and environmental controversies.